Enantioselective Bromocyclization of Allylic Amides Mediated by Phosphorus Catalysis - Kawato, Yuji; Hamashima, Yoshitaka (Synlett, 2018)
Halocyclization of alkenes is commonly employed to increase molecular complexity during organic synthesis because it enables double installation of heteroatoms on a carbon–carbon double bond. Moreover, stereodefined halogenated compounds are widely found among naturally occurring compounds and can serve as versatile chiral building blocks. Therefore, the development of asymmetric halocyclization reactions is of great interest and, in recent years, there has been remarkable progress in catalytic asymmetric halogenation reactions. This account summarizes recent progress made by our group on phosphorus-catalyzed enantioselective bromocyclization of allylic amides. Building on a comprehensive study of the reaction mechanism, we discovered an intriguing catalytic reaction in which P+Br species serves as a fine-tuning element for substrate fixation. We also describe the application of this bromocyclization to asymmetric desymmetrization of 1,4-diene substrates and a concise synthesis of the HIV-protease inhibitor nelfinavir using the newly developed desymmetrization reaction as a key step.1 Introduction2 Enantioselective Bromocyclization of Allylic Amides with a BINAP Catalyst2.1 Bromocyclization with a P/P Catalyst2.2 Bromocyclization with a P/P=O Catalyst3 Desymmetrization of Bisallylic Amides through Enantioselective Bromocyclization3.1 Desymmetrization of Bisallylic Amides3.2 Enantioselective Synthesis of Nelfinavir4 Summary
Keywords: asymmetric synthesis; halogenations; electrophilic addition; alkenes; desymmetrization; heterocycles